2007
DOI: 10.1063/1.2446420
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of resistive double tearing modes with broad linear spectra

Abstract: The nonlinear evolution of resistive double tearing modes (DTMs) with safety factor values q = 1 and q = 3 is studied with a reduced cylindrical model of a tokamak plasma. We focus on cases where the resonant surfaces are a small distance apart. Recent numerical studies have shown that in such configurations high-m modes are strongly unstable and may peak around m = m peak ∼ 10. In this paper, it is first demonstrated that this result agrees with existing linear theory for DTMs. Based on this theory, a semi-em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…The early evolution begins with a linear phase followed by one where low-m modes are nonlinearly driven by the faster high-m modes. These stages were discussed in detail in [33,34] and are found to be similar here. Thus, in the following, we focus on the subsequent fully nonlinear regime.…”
Section: Nonlinear Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The early evolution begins with a linear phase followed by one where low-m modes are nonlinearly driven by the faster high-m modes. These stages were discussed in detail in [33,34] and are found to be similar here. Thus, in the following, we focus on the subsequent fully nonlinear regime.…”
Section: Nonlinear Resultssupporting
confidence: 58%
“…The results for q s = 2 DTMs are directly applicable to other values of q s [13]. This includes cases with nearby q s = 1 resonant surfaces for which the dynamics of resistive DTMs were recently described in [34]. The relaxation of the q profile is generally of practical interest for issues of current profile control, plasma stability and confinement.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is found that the smaller the ∆r, the more easily the transition to PDM can be triggered. In previous researches, [16,17] it is found that in small ∆r the high-m modes may dominate over low-m modes and the DTM has broad linear spectra. However, in these contributions, the effects of the plasma beta are not included due to the limitation of the reduced MHD model.…”
Section: Simulation Results and Discussionmentioning
confidence: 94%
“…[13][14][15] For sufficiently closed rational surfaces, high-m modes may dominate over low-m modes and the DTM has broad linear spectra. [16,17] Other effects on DTM, such as toroidal or poloidal shear flows, [18] Hall effect, [19] guiding field, [20] viscosity, [21] anomalous electron viscosity effect, [22] and self-induced Alfven resonance, [23] have also been investigated.…”
Section: Introductionmentioning
confidence: 99%